An observational study of adherence to combined oral contraceptive regimens. (1st February 2017) - Bastianelli, Carlo; Farris, Manuela; Bruno Vecchio, Roberta Costanza; Rosato, Elena; Guida, Maurizio; Benagiano, Giuseppe
Abstract: Objective : To analyze adherence to an oral contraceptive (OC) regimen and correlate results to participants' socio-demographic and behavioral characteristics. Methods : Women were prospectively enrolled and followed for 6 months. At enrollment, subjects were given a card for recording daily pill intake; its completion was checked at 6 months when women completed a self-administered questionnaire. Results : Out of 755 eligible subjects, 704 agreed to participate; 402 women completed 6 months of recording of use of an OC and properly filled the questionnaire. Good adherence was reported by 64% of participants; 20.9% missed one pill and 14.9% missed more than one pill. Mean number of missed pills per subject was 0.59 and mean number of pills delayed for less than 24 h was 1.18. Best adherence to a COC regimen was associated with evening time intake ( p  = 0.0019). No statistically significant associations of adherence with socio-demographic characteristics were found. Age was only marginally associated with having missed at least one pill. Conclusion : In the present study, a lower number of missed pills were observed than previously reported, but the proportion of missed pills was similar. No association with specific subject characteristics that could serve as markers of increased risk of nonadherence was found.